2021
DOI: 10.1371/journal.pone.0243595
|View full text |Cite
|
Sign up to set email alerts
|

Extreme value theory as a framework for understanding mutation frequency distribution in cancer genomes

Abstract: Currently, the population dynamics of preclonal cancer cells before clonal expansion of tumors has not been sufficiently addressed thus far. By focusing on preclonal cancer cell population as a Darwinian evolutionary system, we formulated and analyzed the observed mutation frequency among tumors (MFaT) as a proxy for the hypothesized sequence read frequency and beneficial fitness effect of a cancer driver mutation. Analogous to intestinal crypts, we assumed that sample donor patients are separate culture tanks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…in a related study [21], the DBFE of synonymous mutations in Hsp90 was found to be heavy-tailed in several environments with α > 2 in most cases. A heavy-tailed DBFE has also been detected among mutations in tumors [12]. A common pattern in many of these results is that the DBFE becomes broader in novel and challenging environments.…”
Section: Tails Of Empirical Dbfesmentioning
confidence: 89%
“…in a related study [21], the DBFE of synonymous mutations in Hsp90 was found to be heavy-tailed in several environments with α > 2 in most cases. A heavy-tailed DBFE has also been detected among mutations in tumors [12]. A common pattern in many of these results is that the DBFE becomes broader in novel and challenging environments.…”
Section: Tails Of Empirical Dbfesmentioning
confidence: 89%
“…in a related study [21], the DBFE of synonymous mutations in Hsp90 was found to be heavy-tailed in several environments with α > 2 in most cases. A heavy-tailed DBFE has also been detected among mutations in tumors [12]. A common pattern in many of these results is that the DBFE becomes broader in novel and challenging envi-ronments.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…The cases of the Gumbel and Weibull extremevalue distributions have been explored in some detail for k = 2 [5][6][7]. The Fréchet EVT class had been conjectured to be relatively unimportant biologically [7], but several subsequent studies [9][10][11][12] have uncovered signatures of heavy-tailed distributions of fitness effects (see SI for further details on tails of empirical DBFEs). In the realistic case of a large number of available beneficial mutations n, the statistics of P k for heavy-tailed distributions of the form (2) is markedly different from that of light-tailed distributions, as will be shown below.…”
Section: Introductionmentioning
confidence: 99%